2020
DOI: 10.1002/acn3.51044
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of FK866 against traumatic brain injury: Involvement of p38/ERK pathway

Abstract: Objective: FK866 is an inhibitor of nicotinamide phosphoribosyltransferase (NAMPT), which exhibits neuroprotective effects in ischemic brain injury. However, in traumatic brain injury (TBI), the role and mechanism of FK866 remain unclear. The present research was aimed to investigate whether FK866 could attenuate TBI and clarified the underlying mechanisms. Methods: A controlled cortical impact model was established, and FK866 at a dose of 5 mg/kg was administered intraperitoneally at 1 h and 6 h, then twice p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…47 The NAMPT inhibitor FK866 can also diminish cell apoptosis by upregulating Bcl-2 and reducing Bax expression in traumatic brain injury. 48 Consistent with these findings, our data suggested that NAMPT siRNA (si-NAMPT) could repress cell apoptosis in IL-1β-treated CHON-001 cells by reducing the ratio of Bax to Bcl-2 (Supporting Information: Figures S2D,E). More importantly, we proved, for the first time, that circ-NT5C2 involved the post-transcriptional regulation of NAMPT by functioning as a ceRNA for miR-142-5p.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…47 The NAMPT inhibitor FK866 can also diminish cell apoptosis by upregulating Bcl-2 and reducing Bax expression in traumatic brain injury. 48 Consistent with these findings, our data suggested that NAMPT siRNA (si-NAMPT) could repress cell apoptosis in IL-1β-treated CHON-001 cells by reducing the ratio of Bax to Bcl-2 (Supporting Information: Figures S2D,E). More importantly, we proved, for the first time, that circ-NT5C2 involved the post-transcriptional regulation of NAMPT by functioning as a ceRNA for miR-142-5p.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the NAMPT inhibitor FK866 can increase anti‐apoptotic Bcl‐2 expression and reduce proapoptotic Bax level, thereby reducing permanent damage in spinal cord injury 47 . The NAMPT inhibitor FK866 can also diminish cell apoptosis by upregulating Bcl‐2 and reducing Bax expression in traumatic brain injury 48 . Consistent with these findings, our data suggested that NAMPT siRNA (si‐NAMPT) could repress cell apoptosis in IL‐1β–treated CHON‐001 cells by reducing the ratio of Bax to Bcl‐2 (Supporting Information: Figures ,).…”
Section: Discussionmentioning
confidence: 99%
“…For the miRNAs differentially expressed in DepTBI vs. ComC ( Table 2A ) there were 11 overlapping canonical pathways ( Figure 5A ), 4 of which are relevant to TBI: ephrin receptor, axonal guidance, BMP, and RhoA signaling ( Frugier et al, 2012 ; Patel et al, 2017 ; Bi et al, 2019 ; Divolis et al, 2019 ; Zhao et al, 2019 ; Greer et al, 2020 ; Mulherkar and Tolias, 2020 ; Duman et al, 2021 ). Likewise, for the miRNAs differentially expressed in DepTBI vs. DepC ( Table 2C ) there were 20 overlapping canonical pathways ( Figure 5C ), 8 of which are relevant to TBI: ERK/MAPK, TGF-β, senescence, reelin signaling in neurons, Wnt/β-catenin, eIF4 and p70S6K, PAK, and cyclins and cell cycle regulation ( Di Giovanni et al, 2005 ; Chen et al, 2007 ; Zhao et al, 2011 ; Salehi et al, 2018 ; Divolis et al, 2019 ; Sen, 2019 ; Dal Pozzo et al, 2020 ; Hascup and Hascup, 2020 ; Sharma et al, 2020 ; Tan et al, 2020 ; Schwab et al, 2021 ). Interestingly, many of these pathways are inter-related.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the p38 MAPK signal pathway can trigger apoptosis via a variety of downstream pathways, such as p53 phosphorylation ( 52 ), activation of caspase cascades and inhibition of anti-apoptotic proteins, such as Bcl-2( 53 ). The phosphorylation of p38 MAPK was reported to accelerate caspase-3 cleavage and increase the Bax/Bcl-2 ratio in a model of traumatic brain injury ( 54 ). The present study demonstrated that H 2 could reverse the increase in p-p38 MAPK expression by vmPFC neurons.…”
Section: Discussionmentioning
confidence: 99%